2003
DOI: 10.1046/j.1471-4159.2003.02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Rho GTPases by synaptic transmission in the hippocampus

Abstract: Ras-related GTPases of the Rho family, such as RhoA and RhoB, are well-characterised mediators of morphological change in peripheral tissues via their effects on the actin cytoskeleton. We tested the hypothesis that Rho family GTPases are involved in synaptic transmission in the CA1 region of the hippocampus. We show that GTPases are activated by synaptic transmission. RhoA and RhoB were activated by low frequency stimulation, while the induction of long-term potentiation (LTP) by high frequency stimulation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 27 publications
(27 reference statements)
0
34
0
Order By: Relevance
“…؊/؊ mice have reduced short-term plasticity We previously demonstrated that LTP induction by HFS is associated with specific activation of RhoB via NMDA receptor stimulation (O'Kane et al, 2003b). Here, we show that while basal levels of synaptic transmission are normal, short-term plasticity was impaired in RhoB Ϫ/Ϫ mouse hippocampus.…”
Section: Rhobmentioning
confidence: 48%
See 2 more Smart Citations
“…؊/؊ mice have reduced short-term plasticity We previously demonstrated that LTP induction by HFS is associated with specific activation of RhoB via NMDA receptor stimulation (O'Kane et al, 2003b). Here, we show that while basal levels of synaptic transmission are normal, short-term plasticity was impaired in RhoB Ϫ/Ϫ mouse hippocampus.…”
Section: Rhobmentioning
confidence: 48%
“…RhoA, Rac1, and CDC42 have all been implicated in the development and maintenance of dendritic structures, including spines (Luo et al, 1996;Nakayama et al, 2000;Tashiro et al, 2000). However, as evidence suggests that induction of LTP activates RhoB but not RhoA or Rac1 (O'Kane et al, 2003b), the hypothesis that RhoB mediates altered spine morphology during plasticity is attractive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalirin, a GEF homologous to GEFT in the Dbl homology and pleckstrin homology domains, has been shown to regulate dendritic spine formation in hippocampal neurons in response to ephrin stimulation (41). In addition, it has been demonstrated that the Rho family of small GTPases is activated by synaptic transmission during both low frequency stimulation and long term potentiation in the hippocampus (42). Within the cerebellum, granule cells function by sending excitatory bifurcate axons along the cerebellar cortex in the parallel fiber pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Rho GTPase activation (34), increase in spine F-actin content (6), and morphologic changes of spines (4,5), are associated with LTP. In addition, the pharmacological manipulation of Rho GTPases affects LTP (35).…”
Section: Enhancement Of Hippocampal Neurotransmission In Cnf1-treatedmentioning
confidence: 99%